Nonanticoagulant Strategies for Venous Thromboembolism Prophylaxis - Gurumurthy, Gerard; Thachil, Jecko (Seminars in Thrombosis and Hemostasis, 2025)
Venous thromboembolism (VTE) remains a major cause of preventable morbidity and mortality. Prophylaxis with anticoagulation is limited by bleeding risk, contraindications, and patient-specific factors. Interest has therefore grown in alternative or adjunctive nonanticoagulant strategies that can mitigate thrombotic risk without increasing bleeding complications. Aspirin has demonstrated efficacy in both primary and secondary prevention of VTE. Most studies and trials have been undertaken in an orthopaedic population but with favorable safety profile. Statins have been shown to reduce VTE incidence without increased bleeding in several trials. Metformin appears to reduce prothrombotic mechanisms in type 2 diabetes. Observational studies have suggested its use to lower VTE risk. However, randomized data are lacking. Glucagon-like peptide 1 receptor agonists (GLP-1 RAs) have been shown to reduce weight, improve metabolic control, and possess anti-inflammatory effects. Evidence suggests GLP-1 RAs may reduce VTE risk. However, findings are inconsistent across observational and trial-based analyses. Other emerging alternatives include hydroxychloroquine, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors (post hoc analyses of cardiovascular trials suggesting lower VTE rates potentially via lipoprotein (a) reduction), sodium-glucose cotransporter-2 inhibitors (overall neutral in meta-analyses of randomized control trials with some real-world evidence vs. comparators), and renin–angiotensin–aldosterone system modulators (mixed observational data and no trial-proven benefit). Uncertainties remain regarding optimal patient selection, duration of prophylaxis, and their role in combination with standard anticoagulation across these drug classes. Further studies/trials are warranted to define the efficacy, safety, and guideline positioning of these agents in diverse patient populations.
Keywords: ACE inhibitor; anticoagulation; aspirin; GLP-1 RA; hydroxychloroquine; metformin; PCSK9 inhibitor; RAAS; SGLT-2 inhibitor; statins; venous thromboembolism; VTE